Penggunaan Media Google Site untuk Meningkatkan Motivasi dan Hasil Belajar IPS pada Peserta Didik Kelas VII SMP - Asih Nuzullailila; Victor Novianto (UM Purwokerto Press, 2022)
Motivation and social studies learning outcomes in class VII students are still low, one of which is because the learning media is less attractive. For this reason, teachers need to make interesting media so that it helps students in learning. Google Site is one of the alternative learning media that can be obtained for free and is easily accessible by students without the need for special applications, can be opened at any time and is not bound by space and time. This research is a type of classroom action research which is carried out in 2 cycles with the object of research being the seventh grade students of SMP. This study aims to improve learning outcomes through the Google Site media. Data collection techniques using test questions, questionnaires and observations. The expected result of this research is an increase in social studies learning outcomes through the Google Site media.